Scope and limitations of ring-opening copolymerization of trimethylene carbonate with substituted γ-thiolactones. Issue 20 (18th April 2018) - Langlais, M.; Coutelier, O.; Moins, S.; De Winter, J.; Coulembier, O.; Destarac, M.
Abstract : The reactivity of functional γ-thiolactones has been investigated in Ring Opening Copolymerization with trimethylene carbonate. Abstract : Functional (co)polymers are increasingly developed by ring-opening polymerization of functional cyclic esters and cyclic carbonates for a wide range of applications. Following this trend and aiming to challenge the polymerization of substituted γ-thiolactones, we studied the ring-opening copolymerization of recently developed γ-thiolactones with trimethylene carbonate in order to prepare new poly(carbonate- co -thioester)s with phosphonated or fluorinated pendant groups.